Pertumbuhan dan Perkembangan Fiqh Lughoh - Abidin, Hasan; Luthfi, Ibnu Mas'ud (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2022)
Fiqh al-lughah is one of the important materials in learning any language, because by studying it a learner can understand the origin of the language, its history and development. The discussion of fiqh al-lughah, in fact, has been widely studied by previous linguists and compiled in one essay, only a very few of them have studied it as a fan of its own knowledge and using a special theme. In addition, some linguists say that ilm al-lughah and philology were originally part of fiqh al-lughah, but with the development of the times and science linguists studied it as a separate study. Through the above background, the author is interested in studying more about fiqh al-lughah specifically and purposefully, with the title: Fiqh Al-Lughah Nasy'atuhu wa Tathawwuruhu. The author's study in this paper is about: Understanding of Fiqh Al-Lughah and Its Purpose, Differences between Fiqh Al-Lughah and Ilm Al-Lughah, Fiqh Al-Lughah in the Earlier Arabic Book and Fiqh Al-Lughah Today and Its Renewal. As for the results of writing this paper through a literature review that the author obtained, namely that: Fiqh Al-Lughah is one of the disciplines that examines the origin of language, its history and development from ancient times to the present in depth and detail, the difference between Fiqh Al-Lughah and Ilm Al-Lughah is that Fiqh Al-Lughah discusses language from the external side while Ilm Al-Lughah from its internal side, as for the fiqh method of Al-Lughah in the earlier books of Language, it started in a natural way not established by someone or someone else, while the discussion at this time was carried out with careful and in-depth study by linguists.